PENGARUH PENERAPAN APLIKASI GAMES WORDWALL TERHADAP KTERAMPILAN MENYIMAK SISWA KELAS V SDN 105292 BANDAR KLIPPA T.A 2023/2024 - Agustina, Rini; Faisal, F; Simanjuntak, Sorta; Sirait, Albert; Wahyu Purnomo, Try (Universitas Negeri Medan, 2024)
This research aims to determine the effect of implementing the Games Wordwall application on listening skills in class V students at SDN 105292 Bandar Klippa, based on problems in the field in the learning process of students not listening well and teachers still using teacher center learning, so the learning process becomes monotonous. This type of research is a quasi-experiment with a Quasi Experimental Design type. Data collection techniques use tests. The subjects in the research consisted of two classes, namely the VA class as the experimental class which would be treated using the Games Wordwall application, totaling 34 and the VB class as the control class not given the same treatment, totaling 32. The average score obtained for the pretest and posttest for the experimental class was from the 40.292 to 81.471 and the average pretest and posttest scores for the control class were from 34.688 to 74.063. The results of this research show that there is an influence of implementing the Wordwall Games application on the listening skills of class V students at SDN 105292 Bandar Klippa. Data analysis used the independent sample T-Test, from the calculation results obtained tcount 4.245 and ttable 1.997 (4.245>1.997), so Ho was rejected and Ha was accepted. However, if we look further at the average pretest and posttest scores, we actually don't see a significant influence between the implementation of the Wordwall Games application and teacher center learning, because they have almost the same range of degrees of improvement.Keywords: Wordwall Games, Listening Skills, Learning Media